2011
DOI: 10.1016/j.chembiol.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Cooperative Ligand Binding by the Glycine Riboswitch

Abstract: Summary The glycine riboswitch regulates gene expression through the cooperative recognition of its amino acid ligand by a tandem pair of aptamers. A 3.6Å crystal structure of the tandem riboswitch from the glycine permease operon of Fusobacterium nucleatum reveals the glycine binding sites and an extensive network of interactions, largely mediated by asymmetric A-minor contacts, that serve to communicate ligand binding status between the aptamers. These interactions provide a structural basis for how the glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 25 publications
6
128
0
Order By: Relevance
“…Stabilization of a junctional region by ligand binding is a recurrent theme in riboswitch RNAs (16,17). The THF riboswitch joins this common trend except that its ligand binds adjacent to the junction, a feature also observed for the glycine riboswitch (18,19). Projection of the THF-induced modulations (2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stabilization of a junctional region by ligand binding is a recurrent theme in riboswitch RNAs (16,17). The THF riboswitch joins this common trend except that its ligand binds adjacent to the junction, a feature also observed for the glycine riboswitch (18,19). Projection of the THF-induced modulations (2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For other tandem riboswitches known, an expression platform follows each aptamer domain (Sudarsan et al 2006;Welz and Breaker 2007). Crystallographic structure determination demonstrates that isolated glycine riboswitch aptamer domains adopt the same fold as in tandem (Huang et al 2010;Butler et al 2011). Moreover, both in solution and in crystals, the isolated aptamer domains show a propensity to oligomerize, utilizing what appears to be the same interface as that used by the tandem aptamers when present in a single RNA chain (Huang et al 2010;Butler et al 2011;Erion and Strobel 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3). This glycine riboswitch is conserved across many bacterial species and occurs upstream of genes encoding proteins of the glycine cleavage system, which facilitates use of glycine as an energy source (Butler et al, 2011;Erion & Strobel, 2011;Huang et al, 2010;Kwon & Strobel., 2008;Mandal et al, 2004;Sherman et al, 2012). In Bacillus subtilis, it has been shown that this riboswitch regulates transcription of the downstream gcvT operon (Mandal et al, 2004;Phan & Schumann, 2007).…”
mentioning
confidence: 99%